Relationship of Soilborne Mycoflora of Cassava Growing Fields to Incidence of Postharvest Rots of Cassava Tubers in Sokoto, Nigeria - Maccido Ibrahim; Kasimu Shehu (Aceh International Journal of Science and Technology, 2014)
In this study the fungi associated with cassava growing fields in Sokoto were isolated and identified using soil dilution technique. A total of 215 fungal colonies from 9 fungal species were isolated from soil samples of different cassava fields between the month of June and August, 2012. It was observed that soil samples from Lambara recorded the highest number (64) of fungal species followed by Damba and the least number (44) of fungal species was observed in Wamakko.The fungi isolated were Alternaria species, Aspergillus niger, Aspergillus fumigatus, Cylindrocarpon lichenicola, Fusarium oxysporum, Geotrichum candidum, Mucor hiemalis, Rhizopus orgyzae and Scopulariopsis candida.The highest percentage frequency of occurrence was observed in Aspergillus niger (39.5%) seconded by Fusarium oxysporum (18.2%) and the least was seen in Rhizopus oryzae ( 2.3%). The pathogenicity test indicated that all the fungal isolates were pathogenic on cassava tubers.The fungus M. hiemalis is the most pathogenic followed by F. oxysporum and the least was recorded by R. oryzae. Therefore, it would be concluded that there is relationship between soilborne fungi and incidence of postharvest rots of cassava tubers.